A step towards accreditation: A robustness test of etching process. (August 2015) - Leonardi, F.; Veschetti, M.; Tonnarini, S.; Cardellini, F.; Trevisi, R.
Abstract: In the present study the robustness of the etching process used by our laboratory was assessed. The strategy followed was based on the procedure suggested by Youden. Critical factors for the process were estimated using both Lenth's method and Dong's algorithm. The robustness test evidences that particular attention needs to be paid to the control of the etching solution's temperature. Highlights: The evaluation of the robustness of the SSNTD etching process (KOH solution 6.0 N, 75 °C, 270 min) have considered several factors. The results evidenced that the etching process can be considered robust. The only critical factor is the etching solution's temperature. A strict control about stability of temperature during the etching process is needed.